2004
DOI: 10.1002/app.20303
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent polymeric materials. XI. Effect of nonionic monomers on the swelling behavior of crosslinked poly(sodium acrylate‐co‐nonionic monomers) in aqueous salt solutions

Abstract: A series of xerogels based on sodium acrylate, nonionic monomers such as 2-hydroxyethyl methacrylate (HEMA) and poly(ethylene glycol) methacrylate (PEGMA), and N,NЈ-methylene bisacrylamide were prepared by inverse suspension polymerization. The results indicate that the water absorbencies for these two gel series were effectively improved by the addition of a small amount of nonionic monomer (HEMA or PEGMA). The initial absorption rates in deionized water were faster for the PEGMA gels than for the HEMA gels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…2,3 The superabsorbent polymeric materials were reported in our previous reports. [4][5][6][7][8][9][10] The monomer used was acrylic acid (AA) with degree of neutralization around 90%.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The superabsorbent polymeric materials were reported in our previous reports. [4][5][6][7][8][9][10] The monomer used was acrylic acid (AA) with degree of neutralization around 90%.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, nonionic surfactants or anion and nonionic surfactants pairs with suitable hydrophile–lipophile balance values have usually been chosen for the stabilizer of inverse suspension polymerization. The synthesized SAPs have usually been particles consisting of beads of various sizes bonded together . In our study, novel SAP particles were fabricated with an anionic–nonionic surfactant (DNS‐1035) as the stabilizer in the inverse suspension polymerization, and the morphologies are shown in Figure (a–c).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the particle size can be regulated with regulation of the stabilizers, agitating rate, and monomer/stabilizer ratio . Some researchers reported that their prepared SAPs with nonionic surfactants or composites of nonionic surfactants and anionic surfactants as stabilizers had excellent water absorptions, fast Q t s, and good resistance to NaCl solutions . For example, Choudhary reported that SAPs with nonionic surfactants as the stabilizer showed good absorbency both in water and NaCl solutions and under load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superabsorbents are slightly crosslinked hydrophilic polymers with three‐dimensional structures that can absorb and retain large amount of water or other biological fluids 1–3. Because of their excellence in water absorbency compared with traditional water absorbing materials, superabsorbents have been widely used in many fields, such as medical treatment, sanitation, water treatment, horticulture, agriculture, and forestry 4–6. Since the first superabsorbent hydrogel was reported by the U.S. Department of Agriculture in 1961,7 tremendous effort has been made to improve their swelling capability, gel strength, and absorption rate 8, 9.…”
Section: Introductionmentioning
confidence: 99%